Problems Of Implementation Of Electronic Land Certificate Arrangements As Debt Guarantee - Pakpahan, Kartina; Azharuddin; Leviyanti (Prophetic Law Review, 2022)
The implementation of land registration and electronic mortgage installation is intended to provide efficiency to rights holders and related agencies in carrying out activities in the land sector. This study aims to determine the positive law regarding the legal certainty of the parties to the electronic land certificate which is used as debt guarantee and the role of the Notary/Official Certifier of Title Deeds in the implementation of the installation of mortgage rights. Using library research, normative juridical methods, analyzing data with a qualitative approach. The Minister of Agrarian and Spatial Planning/Head of the National Land Agency realizes digital-based land registration activities as stipulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 1 of 2021 whose implementation has been postponed. Land-electronic certificates can be used as collateral for debtors' debts by making a deed of granting mortgage which is made and signed before the Land Deed Maker Officer which is then registered at the local National Land Agency Office. The Electronic Mortgage System is implemented as stated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 9 of 2019, the results of the mortgage certificate are in the form of printed electronic documents.Keywords: electronic land registration, notary/land deed maker officer. Permasalahan Pelaksanaan Pengurusan Sertifikat Tanah Elektronik Sebagai Penjaminan Hutang Abstrak Penyelenggaraan pendaftaran tanah dan pemasangan hipotek elektronik dimaksudkan untuk memberikan efisiensi kepada pemegang hak dan instansi terkait dalam melaksanakan kegiatan di bidang pertanahan. Penelitian ini bertujuan untuk mengetahui hukum positif mengenai kepastian hukum para pihak atas akta tanah elektronik yang dijadikan jaminan utang dan peran Notaris/Pejabat Pemberi Sertifikat Hak Tanggungan dalam pelaksanaan pemasangan hak tanggungan. Menggunakan penelitian kepustakaan, metode yuridis normatif, menganalisis data dengan pendekatan kualitatif. Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional merealisasikan kegiatan pendaftaran tanah berbasis digital sebagaimana diatur dalam Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 1 Tahun 2021 yang pelaksanaannya telah ditunda. Sertifikat tanah-elektronik dapat dijadikan jaminan utang debitur dengan membuat akta pemberian hak tanggungan yang dibuat dan ditandatangani di hadapan Pejabat Pembuat Akta Tanah yang kemudian didaftarkan pada Kantor Badan Pertanahan Nasional setempat. Sistem Hak Tanggungan Elektronik dilaksanakan sebagaimana tertuang dalam Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 9 Tahun 2019, hasil sertifikat Hak Tanggungan berupa elektronik tercetak. dokumen.Kata kunci: pendaftaran tanah elektronik, notaris/petugas pembuat akta tanah.